Strategies for Writing Interesting and Informative Book Reviews to Build Social Awareness - Wahyu Febri Ramadhan Sudirman; Paisal Paisal; Syafnur Muhammad Rizki; Muhammad Arif (Journal of Community Service and Empowerment, 2026)
The development of digital technology and social media has influenced the literacy patterns of Generation Z, which tend to reduce in-depth reading habits and critical thinking skills. This condition has resulted in a low social awareness among the younger generation in responding to increasingly complex social issues. One potential critical literacy strategy to address this problem is writing book reviews, as it can train analytical skills, reflection, and the systematic delivery of ideas. However, the skill of writing engaging and informative reviews remains a challenge due to a lack of mentoring and the perception that book reviews are academic and lack context. This community service activity aims to provide training and practical guidance to Generation Z in writing critical book reviews relevant to social issues. The methods used included material delivery, interactive discussions, and review writing practice. The results of the activity demonstrated an increased understanding of the structure, techniques, and function of book reviews as a medium for social reflection. This activity is expected to foster a culture of critical literacy and strengthen Generation Z's social awareness through educational, communicative, and responsible writing.